The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8bm00125a
|View full text |Cite
|
Sign up to set email alerts
|

Taxol-modified collagen scaffold implantation promotes functional recovery after long-distance spinal cord complete transection in canines

Abstract: Treatment of spinal cord injury (SCI) remains a clinical challenge worldwide because of the complicated inhibitory microenvironment formed post-injury, reduced axonal regenerative ability of spinal cord neurons, and scarcity of endogenous neurogenesis within the lesion center. Taxol, in addition to stabilizing microtubules, has shown potential for decreasing axonal degeneration and reducing scar formation after SCI in rodents. In this study, we further verified the therapeutic effects and clinical potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Epothilones act similarly but are preferred because they cross the blood-brain barrier (Ruschel et al, 2015). In a plethora of studies published over the past several years, microtubule-stabilizing drugs have been shown to augment nerve regeneration in the culture dish as well as animal models, even leading to partial recovery of function in rats with injured spinal cords (Hellal et al, 2011;Sengottuvel et al, 2011;Ruschel et al, 2015;Li et al, 2017;Ruschel and Bradke, 2018;Sandner et al, 2018;Yang et al, 2018;Yin et al, 2018). However, an independent attempt failed to achieve notable regeneration or functional recovery, with only modest improvements apparently attributable to the effects of the drugs on non-neuronal cells contributing to the glial scar (Popovich et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Epothilones act similarly but are preferred because they cross the blood-brain barrier (Ruschel et al, 2015). In a plethora of studies published over the past several years, microtubule-stabilizing drugs have been shown to augment nerve regeneration in the culture dish as well as animal models, even leading to partial recovery of function in rats with injured spinal cords (Hellal et al, 2011;Sengottuvel et al, 2011;Ruschel et al, 2015;Li et al, 2017;Ruschel and Bradke, 2018;Sandner et al, 2018;Yang et al, 2018;Yin et al, 2018). However, an independent attempt failed to achieve notable regeneration or functional recovery, with only modest improvements apparently attributable to the effects of the drugs on non-neuronal cells contributing to the glial scar (Popovich et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, collagen hydrogels from skin or tendons usually suffer from poor mechanical strength and resistance to enzymatic degradation due to the relatively weak physical cross‐linking during hydrogel preparation. Hence, collagen hydrogels are often modified by various methods, for instance, dehydrothermal treatment (DHT), ultraviolet irradiation (UV), plasma modification, glutaraldehyde modification and 1‐ethyl‐3‐(3‐dimethyl aminopropyl) carbodiimide (EDC) . However, the treatment with UV or plasma only modifies the surface of collagen, DHT or EDC treatment plays a limited role in promoting the cross‐linking density, and the toxic nature of aldehyde compounds in glutaraldehyde prohibits its application in the process of preparing collagen‐based biomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…Previous methods of Taxol administration for SCI therapy include osmotic minipumps (PerezEspejo et al, 1996) and modified collagen scaffolds (Fan et al, 2018;Yin et al, 2018). In our study, we devised the FGL-functionalized SAP nanofiber scaffold, i.e., FGLmx, for Taxol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Taxol, an FDA-approved anticancer drug, alters microtubule acetylation and promotes microtubule stabilization (Prota et al, 2013). Taxol remarkably increases axonal growth after SCI and protects cultured neurons from axonal retraction following axotomy (Baas et al, 2016;Fan et al, 2018;Yin et al, 2018). Moreover, Taxol also restores the axonal growth potential in the presence of inhibitory molecules (e.g., Nogo-A and CSPGs) (Sengottuvel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%